Titanium and Zirconia Implants and Market - Alexandru - Ionut BUZATU; Georgiana MOICEANU; Olivia Negoita; Andreea BARBU; Mirona POPESCU (Communications of International Proceedings, 2020)
In recent years, the dental implant market has grown significantly due to high demand. The main dental implants are commercially pure titanium (cpTi - grade 4) and zirconia (ZiO2). The aim of this paper is to analyze performances of both dental implants, in terms of mechanical and biological properties, and their growth on global market. Moreover, the paper follows the results of comparing the two dental implamts, in order to decide which one is more suitable.
Keywords: Titanium Implants; Zirconia Implants; Market Demand; Implant Price.